A ciranda das crianças fazendo ciência em um espaço público a praça Dr. Chaves - Montes Claros (MG) - Guimarães, Jussara Maria de Carvalho (2007)
The theme that prays presented, he/she concerns the Perception of the Children five years old in relation to a public space - the Square Doctor Chaves located in the city of Montes Claros/MG/Brazil, considered the Historical Nucleus and origin of the city. We highlighted as objective headquarters of this work, to investigate that perceptions have the five year-old children on the environment, delimiting a specific space - the square and to deepen the referring studies to the Environmental Education in the Infantile Education. As specific objectives, we selected: to observe the five year-old children\'s perceptive activities in a public space; to characterize the environmental perceptions of a same space for children of different social classes and to verify the children\'s of a same age perceptions is differentiated for they belong to teaching nets and classes different social Para the attainment of these objectives it was necessary the use of a specific methodology because, to develop researches with children is not easy task and we needed to understand what the children speak starting from your own constructions, through your world of fantasies. Besides, to understand them starting from our vision, of who is not more child, it constitutes a challenge. Starting from this understanding the investigation based on an approach methodological beginning that extols the previous suspension of every judgment on the domain of the knowledge in consideration, whose qualitative aspects don\'t try they were meditated, using as instruments for the collection of data the structured interview composed of six open subjects and drawing analysis formed an alliance with the in an oral way. They were subject of the research 88 children belonging to 4 Municipal Centers of Infantile Education - located CEMEI in outlying areas of Montes Claros / MG and 83 children of 2 institutions of Infantile Education of the Net Peculiar of teaching located in central areas of the referred city. The choice for children in this age group is justified for they possess quite representative manifestations in relation to your capacities, talents, desires and for possessing a very peculiar way to notice and to explain the facts, to face situations demanded by this phase of the development. Besides, we detached that with 5 years the child already possesses marks of your individuality, your relationships with the healthy middle very personalized, you/he/she tends to be realistic, concrete, you/he/she already uses the speech, the drawing, to clear your perception that has of the world that the fence the Thesis is structured in five chapters, being: Chapter I \" One listens historical of the child and of the Childhood. It was once. . . \". Chapter II the Perception decoded by the environmental reading; the Chapter III \" Of the scribble to the line - of the line to the form - the infantile \" drawing. Chapter IV \" Of the the philosophers\' square to the current Square \"; the Chapter V \" the children\'s Dance in circles making Science in a public \" space The obtained results demonstrated that the five year-old children possess perceptions differentiated for they belong to social classes and teaching nets differentiated. The belonging to a lower social level (Group 1) they didn\'t know the Square Dr. Keys, but they play at close squares to your residences with certain frequency accompanied or not of the parents. The children belonging to the high social class (Group 2) they know the Square Dr. Keys, they play in this square rarely in your parents\' company, but they don\'t play at other squares or there are not close squares to your residences. The children of the Group 1 notice the square as a place to play and full of innovations and the children of the Group 2 as a place to walk and for they already know this place they didn\'t demonstrate a lot of curiosity. In both groups, the square represents a place for the leisure whose function is intimately interlaced with the social conditions of use of this space. For such a study, we articulated our thought in several areas of the knowledge as, the Geography, the Pedagogy, the Sociology, the Philosophy, the Psychology, looking for to base and to speculate the subject.